An annual growth model of the U.S. economy - Hickman, Bert G.; Coen, Robert M. (Amsterdam ; New York : North-Holland Pub. Co., 1976)
This is a new macro-economic model for studying the medium-term growth path of the U.S economy
Includes index.
Includes bibliographical references: p. [277]-279.
oo 23/08/2018
Loans
Keywords: Economics; United States